Stakeholder Integration in Service Innovation - Jonas, Julia M. (Markt- und Unternehmensentwicklung Markets and Organisations, 2018)
Julia M. Jonas examines stakeholder integration and its' dynamics in the setting of service innovation in IT and manufacturing firms. Applying a service-dominant logic theory approach, the multiple case study research describes the implementation of stakeholder integration with its' complexity and challenges. The case analysis provides evidence how stakeholder integration is embedded in service systems, how it is influenced by the surrounding service systems and how it can create effects going beyond the integrated stakeholders. Contents The service-dominant logic perspective on service innovation in service systems Stakeholder integratio n in service innovation: a passive look from outside The management perspective on stakeholder integration in service innovation: a reactively engaged exploration of case study The service systems view on stakeholder integration: a mutually engaged case study on internal stakeholder integration Target Groups Researchers and students of innovation management, organization development, service management, and new service development Product-, innovation-, organization-, and strategy managers The Author Julia M. Jonas works as an innovation management researcher, project manager and lecturer at the University of Erlangen-Nuremberg. She received her PhD in economic sciences from Prof. Dr. Kathrin M. Moeslein at the Department of Information Systems, Chair of Information Systems I - Innovation & Value Creation. .